2019
DOI: 10.14744/nci.2019.47701
|View full text |Cite
|
Sign up to set email alerts
|

A Case Of Autoımmune Hepatitis Following Pegylated Interferon Treatment Of Chronic Hepatitis Delta

Abstract: Autoimmune hepatitis may be frequently associated with chronic hepatitis C (HCV) infection, but there are few case reports regarding hepatitis B and Delta infection (HBV+HDV) as possible triggers. In this report, we present a 44 years old man who was diagnosed as autoimmune hepatitis (AIH) following the treatment of HBV+HDV hepatitis with pegylated interferon (PegIFN). He presented with complaint of fatigue. Laboratory indicated elevated liver enzymes, AST 64IU/L and ALT 112IU/L. The results revealed HBsAg and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…56 Additional cases have been reported by others. 84,85 Thus, features of autoimmune hepatitis should be evaluated before an interferon-based treatment is considered in hepatitis D patients. However, the overall risk for worsening of autoimmune features seems to be low, and resolution of HDV may even reduce IgG levels as one feature possibly associated with autoimmunity.…”
Section: Safe T Y Of Interferon -Ba S Ed Antivir Al Tre Atment In Hep...mentioning
confidence: 99%
See 1 more Smart Citation
“…56 Additional cases have been reported by others. 84,85 Thus, features of autoimmune hepatitis should be evaluated before an interferon-based treatment is considered in hepatitis D patients. However, the overall risk for worsening of autoimmune features seems to be low, and resolution of HDV may even reduce IgG levels as one feature possibly associated with autoimmunity.…”
Section: Safe T Y Of Interferon -Ba S Ed Antivir Al Tre Atment In Hep...mentioning
confidence: 99%
“…Subsequently, in the HIDIT‐I trial one patient had to stop treatment after 12 weeks when an underlying autoimmune hepatitis was demasked during pegylated interferon treatment 56 . Additional cases have been reported by others 84,85 . Thus, features of autoimmune hepatitis should be evaluated before an interferon‐based treatment is considered in hepatitis D patients.…”
Section: Safety Of Interferon‐based Antiviral Treatment In Hepatitis Dmentioning
confidence: 99%
“…In addition to this study, previous reports have shown a positive correlation between pegylated interferon treatment in HBV patients and the induction of AIH in approximately 25%-40%[ 17 ]. Furthermore, isolated cases of patients with hepatitis delta have shown that AIH is also observed after treatment with pegylated interferon[ 18 ]. In contrast, a case of HDV-RNA flare has been reported in a previously negative patient who received immunosuppressive treatment for AIH[ 5 ].…”
Section: Aih Induced By Hdvmentioning
confidence: 99%
“…Daher bleibt die Leberbiopsie zunächst der Goldstandard für die Beurteilung des Stadiums der Leberfibrose bei Patienten mit chronischer HDV-Infektion ohne eindeutige klinische, labortechnische oder bildgebende morphologische Anzeichen einer Leberzirrhose. Darüber hinaus kann eine Beurteilung der Leberhistologie wichtig sein, um Anzeichen einer autoimmunen Hepatitis vor der PEG-IFN-Therapie auszuschließen, die bei Hepatitis D auftreten kann [71] und eine Kontraindikation gegen die PEG-IFN-Therapie darstellt [52].…”
Section: Kommentarunclassified